2020
DOI: 10.3390/molecules25112525
|View full text |Cite
|
Sign up to set email alerts
|

Five New Pregnane Glycosides from Gymnema sylvestre and Their α-Glucosidase and α-Amylase Inhibitory Activities

Abstract: Gymnema sylvestre, a medicinal plant, has been used in Indian ayurvedic traditional medicine for the treatment of diabetes. Phytochemical investigation of Gymnema sylvestre led to the isolation of five new pregnane glycosides, gymsylosides A–E (1–5) and four known oleanane saponins, 3β-O-β-D-glucopyranosyl (1→6)-β-D-glucopyranosyl oleanolic acid 28-O-β-D-glucopyranosyl ester (6), gymnemoside-W1 (7), 3β-O-β-D-xylopyranosyl-(1→6)-β-D- glucopyranosyl-(1→6)-β-D-glucopyranosyl oleanolic acid 28-O-β-D-glucopyranosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This compound also showed anti-obesity action on high fat diet fed rats due to its favorable effect on energy expenditure [24]. In addition, a recent study revealed that, five novel pregnane glycosides, derived from the ethanol extract of the stem of Gymnema sylvestre, and named gymsylosides A-E exhibited α-amylase and α-glucosidase inhibitory activities [42].…”
Section: Discussionmentioning
confidence: 99%
“…This compound also showed anti-obesity action on high fat diet fed rats due to its favorable effect on energy expenditure [24]. In addition, a recent study revealed that, five novel pregnane glycosides, derived from the ethanol extract of the stem of Gymnema sylvestre, and named gymsylosides A-E exhibited α-amylase and α-glucosidase inhibitory activities [42].…”
Section: Discussionmentioning
confidence: 99%
“…The used characterization techniques are the same as described elsewhere. [14] corresponding soluble fractions and water layer. Ethyl acetate extract (34 g) was separated on a silica gel column, eluting with gradient solvent system of dichloromethane/MeOH (0-100 % volume of methanol) to give 6 fractions, PSE1-PSE6.…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…The used characterization equipments and detailed experimental procedures are the same as described in our published work. [15]…”
Section: General Experimental Proceduresmentioning
confidence: 99%